Political opinion polling in Spain and Portugal - Wert, José Ignacio (2003)
This article outlines the development of public opinion polls in Spain and Portugal, in particular during the eighties and nineties, so as accurately to describe the maturing of the public opinion poll market in these countries. It looks first at the development of legislation on opinion polls and the way that legislation influenced the opinion poll market in the two countries. It then compares poll forecasts and actual results in parliamentary elections in the case of Spain, and in both parliamentary and presidential elections in the case of Portugal, in order to assess the accuracy of the polls. The writer also examines the way in which, particularly in Spain, the unreliability of poll results led to changes in the methodologies used, in order to improve those results.